PROBLEMS AND PROSPECTS OF ALAU DAM CONSTRUCTION IN ALAU COMMUNITY, KONDUGA LOCAL GOVERNMENT AREA, BORNO STATE, NIGERIA - A., Babagana; B., Dungus; S. A., Bello; B. S., Kolo (European Scientific Journal, ESJ, 2015)
This research focuses on identifying the problems and prospects of Alau dam construction in Alau community on Konduga local government area of Borno state. The construction of the dam though, has contributed to the development of various activities in Alau community, but has also resulted in various problems as well as loss of lives and property, loss of arable agricultural land, forced resettlement and destruction of farmlands leading to low yield. Data was garnered based on questionnaire administration, interviews and observations. The questionnaire was administered based on households, taking 5% of the total of 1154 households; using systematic sampling technique which gives a sample households of 58. Data was collected on the general information of the respondents, problems, threats and benefits of the construction of Alau dam in Alau community. The data was presented in tables and analyses was done by extracting the major occurrences using percentages which then further discussed with recommendations made to harness the prospects and mitigate the problems.